Perinatal depression screening in Australia: A position paper. (29th December 2020) - Hazell Raine, Karen; Thorpe, Karen; Boyce, Philip
Abstract: Perinatal depression can have enduring adverse effects on women and their children and families, incurring substantial ongoing economic and personal costs. A significant proportion of the cost of perinatal depression relates to adverse impacts on the child, most likely mediated through impairment to the mother‐infant relationship. In recognition of this problem, Australia has invested in routine perinatal depression screening. Our previous research produced convergent findings suggesting that expected benefits for children have not yet been realised through perinatal depression screening. We question the potential of including a measure of personality in current perinatal depression screening for identifying maternal mental health problems and suboptimal mother‐infant relationships. This paper reviews our previous research findings within the broader context of perinatal depression screening. We propose a position, that perinatal depression screening in Australia should be redesigned to more precisely detect vulnerable mother‐infant relationships, parenting, maternal mental health, and infant psychosocial and psychological development. Practice change to appropriately target antenatal interventions may more efficiently improve both maternal and child outcomes, thereby contributing to greater efficiency and cost savings for the health system.